Designing FPGA Based Platform for Real Time Hybrid Monitoring Network - جمال خليفة ,; ياسر عمار ,; شاديا محلا, (Latakia University Journal -Engineering Sciences Series, 2022)
In this paper, we propose a methodology to transfer various types of data simultaneously in real time via Ethernet network using UDP/IP protocols. We choose FPGA (Field Programmable Gate Array) circuits to implement the proposed methodology. We test our methodology on a surveillance platform. The platform contains monitoring camera, that can be moved in two directions: horizontal (Pan direction), and vertical (Tilt direction). The position of camera in Pan and Tilt is measured via sensors. A computer located in a geographically remote area controls the movement of the platform remotely and follows the video signal and sensors from the platform. Through Ethernet network, the signal of the cameras and sensors is transmitted from the platform to the computer, and the control signals are transmitted from the computer to the platform. The problematic in this work is resumed in two aspects; implementing UDP/IP protocols in FPGA, and guaranteeing transfer data in both directions without losses.